Atos de referenciação: um estudo sobre a recategorização anafórica correferencial em Chapeuzinho Vermelho - Correia, Patrícia Matos (2020)
Referencing, inserted in the theoretical-analytical scope of Text Linguistics (LT), since the mid-1990s, has been seen as a textual-discursive phenomenon in permanent re-elaboration of referents. Being an activity of (re) elaborating reality (MONDADA; DUBOIS, 2003), from the perspective of sociocognition, the focus of this approach is found in the study of the construction processes of discourse objects. Starting from a paradigm that deals with how language can refer to the world, this research, based on current studies of Text Linguistics (KOCH, 2009), has the general objective of discussing how children, with eight years old, of the 3rd year of elementary education of a municipal school in the city of Paripiranga/BA, in written productions, they use the use of cross-referenced anaphors (APOTHÉLOZ, 2003) to rename the discourse object “Little Red Riding Hood”. The hypothesis of this work is that children in early grades, in written production activities, often use this type of anaphor to recategorize objects of speech “conceived in a sociocognitive-discursive dimension, and not in an intrinsic property dimension of words” (CAVALCANTE et al, 2017, p. 96). For this, we present three specific objectives: (1) to identify and analyze, in texts written by these children of the 3rd year, linguistic forms (or referential expressions) that function as reclassifying anaphors of the “Little Red Riding Hood” speech object; (2) show that this type of anaphor is chosen and justified by ways explained in the text, which serve as clues for the reworking of this referent; (3) to take the teacher of the initial grades of Elementary School to broaden their text view. It is in this perspective that the constant reworking of the objects of speech (referring) puts the act of referring in a process of constitutive stabilization of the categories of place and world (MONDADA; DUBOIS, 2003), under a look of language as a social and cognitive action in interactively constitutive context and text as the very place of interaction (KOCH, 2002). Linked to the above, we present a methodology in which we inform the public about the corpus and the criteria for its investigation and data collection based on corpus linguistics (GIL, 2002; PRODANOV; FREITAS, 2013; MARCONI; LAKATOS, 2017). From the analysis of the corpus, we verified that the co-referential recategorization process does not happen only through explicit lexical mechanisms, but also through implicit ones, involving cognitive, social, cultural issues, since the children bring, in their written texts, previous knowledge to achieve your goals as writers. In view of the results with the analyzes, we found the importance of the referencing process for teaching, especially for the written production in the initial grades of Elementary Education, leading the child to create skills to discuss and write his own text, attributing it senses still in the literacy process.